Population pharmacokinetics and pharmacodynamics of piperacillin and tazobactam administered by prolonged infusion in obese and nonobese patients. (13th May 2015) - Chung, Eun Kyoung; Cheatham, S. Christian; Fleming, Megan R.; Healy, Daniel P.; Shea, Katherine M.; Kays, Michael B.
Abstract The study objective was to evaluate the population pharmacokinetics and pharmacodynamics of piperacillin and tazobactam administered by prolonged infusion in obese and nonobese patients. Twenty‐seven patients (total body weight [TBW], 60 to 211 kg; body mass index [BMI], 19.6 to 72.9 kg/m2) received 4.5 or 6.75 g every 8 hours, infused over 4 hours, and serum concentrations were measured at steady state. Population pharmacokinetic parameters were estimated using NONMEM, and Monte Carlo simulations were performed for three 4‐hour dosing regimens to calculate probability of target attainment (PTA) at ≥50% fT>MIC.A 1‐compartment linear‐elimination model best fit the pharmacokinetic data for piperacillin and tazobactam. Creatinine clearance (CRCL), TBW, and BMI were significantly associated with piperacillin pharmacokinetics, and CRCL was significantly associated with tazobactam pharmacokinetics. Clearance and volume of distribution for piperacillin and tazobactam were significantly different between obese and nonobese patients (P < .05). At MICs ≤ 16 mg/L, PTA was >90% for dosing regimens ≥3.375 g every 8 hours in nonobese patients and ≥ 4.5 g every 8 hours in obese patients. Piperacillin and tazobactam pharmacokinetics are altered in obesity, and 4.5 g every 8 hours infused over 4 hours should be recommended for empiric therapy in obese patients.